Effect of Organic and Inorganic Fertilizers Amendments on Inflorescence and Flower Morphology and Yield of Coconut (Cocos nucifera L.) - Solangi, Abdul Hameed; Iqbal, M. Z.; Shafiq, Muhammad (International Coconut Community, 2014)
A study was conducted at the Plant Introduction Center (PIC), Southern Agricultural Research Center (SARC), Pakistan Agricultural Research Council (PARC), Karachi for the effect of Organic Neem Seed Powder (NSP) and Gliricidia sepium leaves (GSL) and Inorganic (Urea (N), Di-ammonium phosphate (P) and Murait of potash (K), (NPK) Fertilizers Amendments on Inflorescence and flower Morphology and Yield of Coconut. The experiment consist of eight treatments namely; T1 (NPK + NSP + GSL), T2 (NPK+ NSP), T3 (NPK+ GSL), T4 (NSP + GSL), T5 (NPK), T6 (GSL), T7 (NSP), T8 control without treatments. The experiment was laid down as Complete Randomized Block Design replicated three times. The results demonstrated that the number of spikelets with female flowers were significantly high in T1 to T7 as compared to T8 treatment. The 1st spikelets with number of female flowers (48.97) were significantly (p<0.05) high in T1 as compared to T2, T3, T4 and T8. In case of stalk length (38.05 cm) it was significantly (p<0.05) high in T1 as compared to T8. The findings of the study indicated that the number of nuts (99.33) and fruit weight (1490.77 g) were significantly (p<0.05) highest in T1 as compared to T3 to T8 and T2 to T8 treatments, respectively. The T1 treatment also showed better fruit length (25.75 cm), fruit breadth (42.97 cm), husk weight (448.66 g), shell weight (278.11 g), kernel weight (434.22 g) and nut water (188.77 ml) with significant differences in some of the treatments. The application of organic amended with inorganic fertilizers, enhanced the growth and nut production in nutrient deficient soils. It is therefore, recommended that treatment T1 NPK+NSP+GSL)/palm/year was enough to improve the morphological, inflorescence, flower morphology, high nut production, better income to coconut farmers, economical and beneficial for conservation of coconut genetic resources in coastal area of Pakistan.